The impact of zero equivalence on translation with special reference to English and Xitsonga - Mabunda, Idah (University of Limpopo (Turfloop Campus), 2013)
This study examines the impact of Zero equivalence when translating Xitsonga to English and vice versa. Translation is essential in everyday communication, therefore it is important to choose the accurate equivalent variant during the process if not so misunderstanding occurs especially where the target language has nil elements for a particular concept. In this study semi-structured interview was conducted and it is discovered that in place of zero equivalent variants different strategies were provided by different respondents to overcome the deficiency which target languages experience. Looking for sameness of meaning during communications exposes insufficiency of words, phrases and concepts in translating languages with different culture.
Thesis ( M.A. (African Languages)) --University of Limpopo, 2013.
Keywords: Translation; 496.3978; Translating and interpretation; Language and languages -- Grammar; Tsonga language